Comparative Studies of CSEB by Using RHA and Lime as a Partial Replacement of Cement - Yadav, Kalpana; Shrestha, Bimala; Giri, Anusha; Gurung, Kiran; Karki, Bipashwi; KC, Asmita; Bhandari, Gyanendra (OCEM Journal of Management, Technology & Social Sciences, 2024)
In the growing concerns about sustainable building materials and environmental issues, Compressed Stabilized Earth Brick (CSEB) emerges as a notable solution. CSEB is recognized for its energy efficiency, cost-effectiveness, and eco-friendliness, making significant contribution to sustainable development. Unlike traditional concrete blocks and fired bricks, CSEB production requires less energy, as it involves compressing a mixture of local earth and stabilizers like cement or lime without high-temperature firing. This process reduces carbon emissions and conserves energy resources. Economically, CSEB uses locally sourced materials like RHA/Lime, cutting transportation costs and supporting local economies. Additionally, the simpler production process reduces labour costs. Environmentally, CSEB minimizes waste and the environmental impact of raw material extraction. Overall, CSEB’s properties compare favourably with concrete blocks and fired bricks, offering a robust, sustainable alternative for modern construction. This research investigates the properties and internal mechanisms of soil blocks made with two different materials, specifically rice husk ash (RHA) and lime. Experiments were conducted with the main variables being RHA content at 0.2, 0.4, and 0.6 wt.% and lime content at 0.2, 0.4, and 0.6 wt.%. Tests included Atterberg’s Limit Test, Plasticity Index Test, Soil Type Classification, Water Absorption Test, and Compressive Strength Test. Further investigation with soil blocks of different ratios and compositions concluded that among all the samples, CSEB with lime (20%) as a replacement for Ordinary Portland Cement (OPC) exhibited better water absorption capacity compared to RHA. Additionally, CSEB with lime (20%) as a replacement for OPC demonstrated the highest compressive strength compared to RHA.